Experts’ Perceptions of the Effects of Forest Biomass Harvesting on Sustainability in the Alpine Region - Gianluca Grilli; Giorgio Curetti; Isabella De Meo; Giulia Garegnani; Francesca Miotello; Aleš Poljanec; Daniele Vettorato; Alessandro Paletto (South-East European Forestry, 2015)
Background and Purpose: In the EU political agenda, the use of forest biomass for energy has grown rapidly and significantly, in order to mitigate carbon dioxide emissions and reduce the energy dependence on fossil fuels of European member countries. The target of the EU climate and energy package is to raise the share of renewable energy consumption produced from renewable resources to 20% in 2020 (Directive 2009/28/EC). With regards to biomass energy, the supply of forest wood biomass is expected to rise by 45% (reference period: 2006-2020), in response to increasing demand for renewable sources. The increase of forest biomass supply could have both positive and negative effects on several forest ecosystem services (ESs) and local development. These effects should be assessed in a proper manner and taken into account when formulating management strategies. The aim of the paper is to assess the environmental, economic and social sustainability of forest biomass harvesting for energy, using the Figure of Merit (FoM) approach. Materials and Methods: Sustainability was assessed through a set of four indicators: two focused on experts’ opinions regarding the effects of forest biomass harvesting and the other two focused on the cost-benefit analysis (potential energy obtained and costs for wood chips). The research was developed through four case studies located in the Alpine Region. A semi-structured questionnaire was administered face-to-face to 32 selected experts. The perceived effects of forest biomass harvesting for energy on ESs and local development were evaluated by experts using a 5-point Likert scale (from “quite negative effect” to “quite positive effect”). Results: All experts agree that forest biomass harvesting has a positive effect on forest products provision and local economic development (employment of local workforce, local entrepreneurship and market diversification), while the effects on other ESs are controversial (e.g. carbon sequestration, habitat quality, natural hazards protection and recreational values). Conclusions: Therefore, it can be asserted that the effects of forest biomass harvesting on sustainability vary according to the local context. The results of FoM can support decision makers in order to analyze the environmental, social and economic sustainability of forest biomass harvesting for energy.